Enhancing Elementary School Teachers Competency as Mathematics and Science Olympiad Supervisors - FUADIYAH, SADIATUL (Fakultas MIPA Universitas Negeri Padang, 2024)
Community service activities aim to provide knowledge through coaching to teachers to deepen the material and training on science olympiad questions, thus helping teachers in analyzing, directing and guiding students who will take part in olympiad selection at the district/city, provincial and national levels. The targets for this activity are mathematics and science olympiad supervisor teachers from several elementary schools that are members of the KKG Cluster 3 of Koto Tangah District. The method used in this activity is a direct approach, lecture or practice. The approach method is carried out by observing the problems faced by the supervising teacher. The lecture method is carried out through socialization and coaching related to Olympic material. Meanwhile, the practical method is carried out through training and in-depth study of science olympiad questions. The result of this activity is that teachers are able to analyze, direct and guide students who will take part in the Olympic selection at the district/city, provincial and national levels so that they can improve the quality of education in the Olympic field.